Arctic Yearbook 2015 -- Arctic Governance and Governing - Heininen, Dr. Lassi; Exner-Pirot, Heather; Plouffe, Joël (NRF, 2015)
Preface - Arctic Governance Fran Ulmer “The most important thing for people to know about the governance of the Arctic is that we have a chance now to act to maintain the integrity of the system or to lose it. To lose it means that we will dismember the vital systems that make the Arctic work. It's not just a cost to the people who live there. It's a cost to all people everywhere.” -Sylvia Earle Governance is “the processes of interaction and decision-making among the actors involved in a collective problem that lead to the creation, reinforcement, or reproduction of social norms and institutions.”2 In short, it’s the effort to make good decisions for society.